Dynamics Assistance For Learning Pandemic Time Covid-19 in Tukmudal Village, Sumber Cirebon - Ridwan, Taufik (Devotion : Journal of Research and Community Service, 2019)
Learning is an important instrument to educate the nation's life. As an important system in education, learning is organized as an interaction space for the building of teacher and student relationships to develop cognitive, psychomotor and affective potential. This must be supported by the dynamics of learning that run effectively and an internal learning atmosphere that makes students interested in learning. Learning can also be influenced by external factors, such as the Covid-19 outbreak. The reality shows that the learning dynamics in Tukmudal village are currently being disrupted by the Covid-19 outbreak which has had an impact, including; 1) schools are transferred to homes through an online learning process; 2) there is a transformation of technology-based learning media through the use of Wathshap Group, Zoom, Google Classroom, WebEx, Youtube, and TV channels (TVRI); 3) adjustment of learning methods; 4) adjusting the learning evaluation to determine the standards for class promotion and graduation; and 5) demands for collaboration between parents of students at home as a substitute for teachers to control children's learning.